Sustainability in Historical Islamic Architecture: Lessons from Sheikh Lotfollah Mosque’s Construction Techniques - Naghipour, Peyman; Naghipour, Afshin; Shirdel, Amir Hossein; Behzadi, Sara Zanganeh; Rahaei, Omid; Salamati, Samaneh (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2025)
This research examines the construction techniques and principles of sustainability in the architecture of Sheikh Lotfollah Mosque, one of the most prominent examples of Islamic architecture. The main goal is to identify the sustainability elements of this mosque, emphasizing the use of local materials and traditional methods so that it can be presented as a model for contemporary architecture. The research deals with environmental challenges and the need to design sustainable buildings in today's world, which is faced with a decrease in natural resources and an increase in demand. In this regard, the research questions are: 1- What construction and architectural techniques have been used in the Sheikh Lotfollah Mosque that have contributed to its stability and durability over time? 2- How can the sustainability techniques in the architecture of Sheikh Lotfollah Mosque be used as a model for the design of contemporary buildings? The method of this research is considered interpretative-historical. Its content has been prepared and adjusted using descriptive-analytical and library-documentary studies as well as field studies. The findings show that the Sheikh Lotfollah Mosque has achieved stability and durability by using architectural techniques in accordance with climatic conditions. The conclusion emphasizes that the principles of Islamic architecture, especially the use of local materials and environmentally friendly methods, can inspire contemporary architecture. The implications of this research include providing practical models for today's architects who seek to design sustainable and environmentally friendly buildings. The key contribution of this research is in reviving traditional techniques and matching them with new technologies. The novelty and originality of this research is that, for the first time, it has carefully examined Sheikh Lotfollah Mosque from the perspective of sustainability and links these concepts to contemporary architecture, which can be influential in the design of future buildings.